Rapid, high-resolution 14C chronology of ooids - Beaupré, S.; Roberts, M.; Burton, J.; Summons, Roger (Elsevier Ltd, 2015)
Ooids are small, spherical to ellipsoidal grains composed of concentric layers of CaCO3 that could potentially serve as biogeochemical records of the environments in which they grew. Such records, however, must be placed in the proper temporal context. Therefore, we developed a novel acidification system and employed an accelerator mass spectrometer (AMS) with a gas accepting ion source to obtain radiocarbon (14C) chronologies extending radially through ooids within one 8-h workday. The method was applied to ooids from Highborne Cay, Bahamas and Shark Bay, Australia, yielding reproducible 14C chronologies, as well as constraints on the rates and durations of ooid growth and independent estimates of local 14C reservoir ages.